Protective Effect of Psidium guajava Leaf Extract on Altered Carbohydrate Metabolism in Streptozotocin-Induced Diabetic Rats. (1st December 2013) - Khan, Haseena Banu Hedayathullah; R, Shanmugavalli; Rajendran, Deepa; Bai, Mookambikai Ramya; Sorimuthu, Subramanian
ABSTRACT Psidium guajava is an important plant of high medicinal value and has been used in traditional systems of medicine against various ailments. The antidiabetic effect of the ethanolic extract of Psidium guajava leaves and also its protective effect on altered glucose metabolism was evaluated in streptozotocin (stz)-induced diabetic rat model. Diabetes was induced in rats by means of intraperitoneal injection of 50-mg/kg body weight (b.wt.) of stz. Diabetes-induced rats were randomly divided into two groups. One group of rats was treated with Psidium guajava leaf extract at a dosage of 300-mg/kg b.wt. and the other group of rats was treated with the standard drug glyclazide at a dosage of 5-mg/kg b.wt. for 30 days. The blood glucose levels, plasma insulin, Hb, HbA1c were measured. The effect on the drug on altered glucose metabolizing enzymes were also studied. Treatment with Psidium guajava extract showed a significant reduction in blood glucose and HbA1c levels and a significant increase in plasma insulin levels. The drug also significantly restored the activities of carbohydrate metabolizing enzymes. This suggests that the potential antidiabetic effect of the ethanolic extract of the Psidium guajava leaves may be due to the presence of flavonoids and other phenolic components present in the drug.